Kebijakan dan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru di Sekolah MI Ma’Arif 2 Yogyakarta - Nursiah Nursiah; Lathifatul Maghfiroh (UMSU, 2023)
This study aims to analyze the principal's policy and leadership in improving teacher performance at MI Ma'arif 2 Yogyakarta School. The research was conducted using qualitative methods and collected data through interviews, observations, and document analysis. The results showed that the principal has implemented various policies and effective leadership strategies to improve teacher performance at school. First, the principal creates a comfortable and conducive working atmosphere in the school, including in the teachers' offices, by providing adequate facilities and tidying up the working environment. Second, principals build harmonious relationships between teachers by holding meetings, discussions and social activities. In addition, principals encourage good communication between teachers and students by providing opportunities for students to give feedback to teachers. The principal also acts as a mediator in learning at school, resolving problems or conflicts that may arise between teachers and students. In addition to the implemented leadership policies and strategies, principals also implement supporting programs such as training and workshops to increase teachers' motivation and professional development. Awards and appreciation are given to teachers who achieve good results in learning. And inspire teachers to continuously improve the quality of their teaching.